Methodological Understandings for the Construction of Functional Lexicological Model - Pamela Faber; Ricardo Mairal Usón (Miscelánea: A Journal of English and American Studies)
Although recent work in theoretical linguistics has stressed the important  role of the lexicon within linguistic theory, its description is still too deeplyseated  in theory internal qualifications. Then, it is the aim of this paper to  present the theoretical foundations of a Lexicon/Dictionary which can account for speakers' actual lexical knowledge. These theoretical foundations  have been gathered under the rubric of Functional Lexicology.